Microcircuitry of beta ganglion cells in cat retina - McGuire, BA (J Neurosci, 1986)
We reconstructed from electron micrographs of 189 serial ultrathin sections a major portion of the dendritic tree of an on-beta ganglion cell through its sixth order of branching. One hundred three contacts from three cone bipolar cells were identified. Forty-seven contacts were from a single CBb1 cone bipolar. These were distributed widely over the dendritic tree but were frequently found on the slender “basal tuft” dendrites. Twenty-two additional contacts from a second CBb1 cell were found but not studied in detail. Thirty-four contacts were from a single CBb2 cone bipolar; these also were distributed widely but were primarily on the branches of the main dendritic arborization. A major portion of the dendritic tree of an off-beta cell was also reconstructed through its seventh order of branching. Thirty-five contacts from two cone bipolar cells were identified. Twenty-three contacts were from a single CBa1 cone bipolar and 12 widely distributed over the off-beta cell dendritic tree. We propose that the photopic receptive field center of a beta cell corresponds to the envelope of the receptive fields of the bipolar cells that connect it to the cones. The center response of a beta cell may be generated by a “push-pull” mechanism. For the on-beta cell there would be excitation at light on from CBb1 and disinhibition from CBb2 and the reverse at light off. For the off-beta cell there would be inhibition at light on from CBa2 and withdrawal of excitation from CBa1. Should the bipolars have antagonistic surrounds (so far reported only for CBb1), the beta cell surrounds as well as their centers might be generated by this push-pull mechanism.